1949
DOI: 10.1007/bf02665173
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing vegetable oil bleaching by adsorption

Abstract: Vegetable oil bleaching by adsorption involves the removal of color particles which are either dissolved or colloidally dispersed in the oil. This type of adsorption follows an exponential relationship and the Freundlich equation was utilized in correlating the data. In utilizing this equation, the color of the oil was assumed proportional to the concentration of the color particles, and a color measurement system based on the Beer‐Lambert Law was devised. This system involves a measurement of the transmittanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1966
1966
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…The data in Figures 1 and 2 suggest that the pigment binding abilities of acid ash and acid activated clay were similar. The increase in ash activity after acid activation parallels similar findings in conventional bleaching clays (5). Acid activation of montmorillonite opens up the crystal structure to produce a greater surface area available for adsorption.…”
Section: Resultssupporting
confidence: 77%
“…The data in Figures 1 and 2 suggest that the pigment binding abilities of acid ash and acid activated clay were similar. The increase in ash activity after acid activation parallels similar findings in conventional bleaching clays (5). Acid activation of montmorillonite opens up the crystal structure to produce a greater surface area available for adsorption.…”
Section: Resultssupporting
confidence: 77%
“…Other workers have either assumed or suggested that adsorption of pigments, mainly gossypol and its derivatives, from cottonseed oil follows the Freundlich isotherm (12,14). Those studies involved pigment mixtures and not a pure substance as in the present case.…”
Section: Modeling Of Isothermsmentioning
confidence: 91%
“…• C (12,13,18,19). There are discrepancies about the respective influence of the SiO 2 and Al 2 O 3 contents of adsorbents and their efficiency (14,15,18,19).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations